2007
DOI: 10.1007/s10834-007-9068-5
|View full text |Cite
|
Sign up to set email alerts
|

Employment Behaviors of Mothers Who have a Child with Asthma

Abstract: The effects of having a child with asthma on the employment status and the continuity of full-time employment of mothers were investigated using data from the Medical Expenditure Panel Survey. Mothers who had a child with asthma were less likely to be employed full-time or part-time, and if single, they were less likely to retain their full-time jobs than other mothers. The effects of having a child with asthma depended on the marital status of the mother and the well-being of the child. Employment behaviors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 27 publications
1
32
0
1
Order By: Relevance
“…For example, Buchmueller and Valletta (1999) found that the response to spousal coverage is stronger for women with children in the household. Other studies suggest that the health of children may be a factor in the relationship between family labor supply decisions and health insurance coverage (Baydar et al 2007;Sharpe and Baker 2007), that insurance coverage may be related to labor decisions influenced by informal caregiving for older adults (Wilson et al 2007), and that family labor supply decisions may influence potential substitutes for insurance such as selfcare behaviors (Doumas et al 2008). Also, different types of employer-offered insurance may play a role in family labor supply decisions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Buchmueller and Valletta (1999) found that the response to spousal coverage is stronger for women with children in the household. Other studies suggest that the health of children may be a factor in the relationship between family labor supply decisions and health insurance coverage (Baydar et al 2007;Sharpe and Baker 2007), that insurance coverage may be related to labor decisions influenced by informal caregiving for older adults (Wilson et al 2007), and that family labor supply decisions may influence potential substitutes for insurance such as selfcare behaviors (Doumas et al 2008). Also, different types of employer-offered insurance may play a role in family labor supply decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of individual supports extends to family-of-origin and health characteristics (Acs and Loprest 2001;Baydar et al 2007;Corcoran et al 2004;Edin and Harris, 1999;Gault et al 1998;Hao 1994). In a study of employment patterns among low-income mothers using PSID (1983)(1984)(1985)(1986)(1987)(1988) data, Edin and Harris (1999) showed that family background characteristics, such as increased parental education levels, were positively related to employment among low-income unmarried mothers.…”
Section: Individual and Family Background Supportsmentioning
confidence: 99%
“…Although there has been some longitudinal research, 3 , 15–17 there is very little European evidence 9 , 10 , 18 . In order to investigate these two potential mechanisms, we used longitudinal data from Millennium Cohort Study, a large, contemporary cohort of UK children born in 2000, with information on childhood long-term limiting illness and maternal employment recorded in early to middle childhood.…”
Section: Introductionmentioning
confidence: 99%